Pengaruh Halal Awareness dan Potongan Harga terhadap Perilaku Konsumen Makanan dan Minuman Cepat Saji - Sari, Mega Permata; Rahmat Setia, Mochamad Nur; Mintarsih, Mimin (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
Fast food has become a staple choice for people, especially Muslim millennials. Food halalness is an important consideration for consumers, given the many food options available. Office workers tend to be more consumerist than millennials over the age of 30. However, when shopping, millennials focus on discounts. More than 66% of millennials will switch brands if offered at least a 30% discount, and only a third of them still consider brands to consider trends or product updates to get a discount. This study aims to test whether halal awareness and discounts can affect the behavior of Muslim millennial office worker fast food consumers in Bandung City. This study uses a sample of Muslim millennials who work in Bandung City. The methods used in this study are descriptive and verification methods. The research data was analyzed using data analysis techniques with Frequency Distribution Table, Linear Regression Analysis, Multiple Regression Calculation, Correlation Coefficient Calculation, determination, T Test and F Test. Based on the results of data analysis and hypothesis testing, it was found that Halal Awareness and Discounts have a significant influence on the Behavior of Fast Food Consumers and Drinks on Muslim Millennials in Office Sectors throughout Bandung City.